JavaScript fundamentals I and II - Deitel, Paul J.; Prentice-Hall, inc. ([Upper Saddle River, NJ] : Prentice Hall, 2009)
This program will show you how to start building hot new JavaScript and Ajax applications. Watch and learn core JavaScript techniques, including control statements, functions, arrays, objects, events, CSS, and DOM. Then, building on the basics, master scripting with XML and RSS -- and start building the Ajax-rich Internet applications that are taking the Web by storm.
Title from container.
Instructor, Paul J. Deitel.
System requirements for Windows: 500 MHz or higher CPU; 128 MB RAM or more; Windows 2000/XP/Vista; DVD drive; 1280 x 960 or higher display; sound card with speakers.
System requirements for Macintosh: 500 MHz or higher CPU; 128 MB RAM or more; Mac OS X; DVD drive; 1280 x 960 or higher display; sound card with speakers.
DVD-R643.
Keywords: JavaScript (Computer program language); Web site development